Differential iNKT and T Cells Activation in Non-Alcoholic Fatty Liver Disease and Drug-Induced Liver Injury - Estefanía Caballano-Infantes; Alberto García-García; Carlos Lopez-Gomez; Alejandro Cueto; Mercedes Robles-Diaz; Aida Ortega-Alonso; Flores Martín-Reyes; Ismael Alvarez-Alvarez; Isabel Arranz-Salas; Francisco Ruiz-Cabello; Isabel M. Lucena; Eduardo García-Fuentes; et al. (Biomedicines, 2021)
Background: Non-alcoholic fatty liver disease (NAFLD) and idiosyncratic drug-induced liver injury (DILI) could share molecular mechanisms involving the immune system. We aimed to identify activation immunological biomarkers in invariant natural killer T (iNKT) and CD4/CD8+ T cells in NAFLD and DILI. Methods: We analyzed the activation profile (CD69, CD25, and HLA-DR) and natural killer group 2 member D (NKG2D) on iNKT cells, and CD4/CD8 T cells in peripheral blood mononuclear cells from NAFLD, with or without significant liver fibrosis, and DILI patients. Results: There was an increase in iNKT cells in NAFLD patients compared to DILI or control subjects. Regarding the cellular activation profile, NAFLD with significant liver fibrosis (F ≥ 2) displayed higher levels of CD69+iNKT cells compared to NAFLD with none or mild liver fibrosis (F ≤ 1) and control patients. CD69+iNKT positively correlated with insulin resistance, aspartate aminotransferase (AST) level, liver fibrosis-4 index (FIB4) and AST to Platelet Ratio Index (APRI). DILI patients showed an increase in CD69+ and HLA-DR+ in both CD4+ and CD8+ T cells, detecting the most relevant difference in the case of CD69+CD8+ T cells. Conclusions: CD69+iNKT may be a biomarker to assess liver fibrosis progression in NAFLD. CD69+CD8+ T cells were identified as a potential distinctive biomarker for distinguishing DILI from NAFLD.